Pengaruh Tingkat Hutang Dan Tingkat Kesulitan Keuangan Terhadap Konservatisme Akuntansi (Jurnal Kendali Akuntansi, 2024)
Financial recognition is the basis that encourages companies to report losses early and delay revenue recognition. Conservatism affects the quality of the main indicators reflected in financial reporting. The method used in this research is Structured Literature Review (SLR), where the data sources are obtained from Semantic School, Sinta Journal, and Google School for the publication years 2018 to 2024. Next, filtering is carried out to match the subject matter, resulting in 50 journals that will be analyzed systematically. So the results of the research state that a level of debt has a good influence on financial recognition, even though the level of financial difficulty has a positive but negative effect on accounting conservatism. So it indicates that a manager who has a high level of debt leads to more conservatism in their financial reporting to meet the interests of creditors, while companies experiencing difficulties tend to be less conservative.